European Representative Democracy Data Archive - Andersson, Staffan; Ersson, Svante; Bergman, Torbjörn (Umeå University, 2015)
The European Representative Democracy data archive consists of cabinet-level data for 29 European democracies in post-WWII Europe. For each country it includes data for the cabinets that have formed after the introduction of the current democratic regime of parliamentary democracy (for Cyprus representative democracy). Included are cabinets that have formed before or on December 31 2010. Altogether, a total of 640 cabinets- -coalitions, single party and non-partisan- are included.

Purpose:

The purpose of the data archive project is to rectify a lack of comparable comprehensive data on the relation between citizens' and central actors of representative democracy's views of democratic values and attitudes, and systematic information on central political actors and the institutions in which they exist.

Datasetet i "The European Representative Democracy Data Archive" består av data på regeringsnivå för 29 europeiska demokratier. För dessa länder inkluderas data för samtliga regeringar som bildats från och med att landet övergått till sitt nuvarande demokratiska styrelseskick, och som bildats senast 31:e december 2010. Totalt ingår 640 olika koalitions-, enpartis- och partiobundna regeringar i datasetet.

Syfte:

Syftet med ERDDA-projektet är att åtgärda en rådande brist på jämförbar och omfattande data gällande relationen mellan medborgares demokratiska värderingar och attityder, och systematisk information gällande de centrala politiska aktörerna och institutionerna i deras respektive hemländer.
European Representative Democracy Data Archive
Keywords: state control; statlig styrning; government policy; regeringspolitik; government; regering; political institutions; politiska institutioner; government role; statsmaktens roll; data; data; political systems; politiska system; representative democracy; representativ demokrati; Political behaviour and attitudes; Politiska beteenden och attityder; Government, political systems and organisations; Regering, politiska system och organisationer; Political Science; Statsvetenskap; Political Science (Excluding Peace and Conflict Studies); Statsvetenskap (exklusive freds- och konfliktforskning)